The future of product design - Follett, Jonathan (O'Reilly Media, 2015)
Design and production considerations change throughout any product's lifecycle-from prototype to market introduction, through growth and maturity, and finally into decline-with each stage introducing its own set of challenges. But emerging technologies such as 3D printing, robotics, and the IoT are disrupting every stage of this lifecycle as they reinvigorate existing categories and create entirely new ones. In this report, Jonathan Follett from Involution Studios examines from a designer's perspective the ways emerging technologies are affecting the product lifecycle, and explores various options for companies looking at new ways of approaching product design and development. Today, not only must companies contend with the difficulties of introducing emerging tech into their product portfolio, they must also negotiate a labyrinth of complex factors, as the product design and development cycle itself is remade by these new technologies as well. This report will help you to understand and navigate this new world of product design.